Effects of mGluR5 positive and negative allosteric modulators on brain damage evoked by hypoxia-ischemia in neonatal rats - Makarewicz, Dorota; Słomka, Marta; Danysz, Wojciech; Łazarewicz, Jerzy W. (Folia Neuropathologica, 2015)
In the present study, we examined the effects of negative and positive allosteric modulators of metabotropic glutamate receptor 5 (mGluR5), fenobam and ADX47273, respectively, on brain damage induced by hypoxia-ischemia (H-I) in 7-day-old rats. The test drugs were administered intraperitoneally 10 min after H-I. Rectal body temperature was measured for 2.5 h after the insult. The number of apoptotic neurons in the immature rat brain was evaluated after 24 h. The wet weight of both hemispheres was determined 14 days after H-I, and its loss was used as an indicator of brain damage. In the vehicle-treated groups, H-I reduced the weight of the ipsilateral (ischemic) hemisphere by approximately 33% and sixfold increased the number of apoptotic cells in the cortex. Fenobam (10 mg/kg) and ADX47273 (5, 10, and 30 mg/kg) had no significant effect on brain damage, although application of fenobam at this dose significantly reduced the number of apoptotic cells. In contrast, fenobam (20 mg/kg) potentiated ischemic brain damage to 57.4% and had no effect on H-I-induced apoptosis. In all of the experimental groups, we detected no significant changes in the weight of the contralateral (control) hemisphere or the rectal temperature. In conclusion, in 7-day-old rats, the bidirectional modulation of mGluR5 by fenobam (10 mg/kg) and ADX47273 (all doses tested) did not result in significant changes in H-I-evoked brain damage, supporting our previous data indicating that also the antagonists of mGluR5 MPEP and MTEP, which reduce neuronal lesions in adult animals submitted to brain ischemia, were ineffective in 7-day-old rat pups.